"Language not just as words": Supporting new literacies through a design project in disadvantaged schools in Chile. (March 2021) - Thibaut, Patricia; Carvalho, Lucila
Young people are increasingly connected in a digital and globalized world, but technology-mediated interactions alone do not necessarily lead to a culture of meaningful participation and meaning making processes. Students from disadvantaged contexts are especially vulnerable to this. Drawing on the Activity-Centred Analysis and Design framework this paper discusses a case study situated in disadvantaged schools in Chile. Phase 1 of the study revealed that high school students' literacy practices in the everyday classroom mostly reflected low conceptual and procedural understanding of new literacies, confirming that these young learners enacted passive forms of technological use in and out-of-school spaces. Phase 2 of the study involved the development and implementation of a digital project at a Chilean school. Results offer insights on how alterations in tools, learning tasks, and social arrangements, led to reconfigured literacy practices. Findings also show that the relationship between access, use and outcomes is not straightforward, and students' cultural capital varies, even in disadvantaged schools. Implications of the study stress the pivotal role of schools and the potential of well-orchestrated educational designs, for introducing and encouraging meaningful literacy practices, and for leveling up the access to the digital world.